The Scales of General Well-Being (SGWB) - Longo, Ylenio (2017)
Well-being indicators are often conceptualized either as positive feeling (e.g. happiness), positive functioning (e.g. meaning, involvement, competence), or a combination of the two. Several measures of well-being have been developed based on this distinction, with lower-order factors (e.g. happiness, meaning) loading on separate higher-order factors (e.g. positive feeling and positive functioning). However, some limitations have been identified in the lower-order factor structure of current well-being questionnaires. Furthermore, recent evidence indicates that a single higher-order or general factor adequately explains most of the variation in well-being data. This dissertation presents the development and initial validation of a questionnaire, which attempts to overcome some limitations in the lower-order structure of previous questionnaires and assumes the presence of a single general factor of well-being. Following a review of current measures, commonalities among them were identified and, based on these points of agreement, the general factor was conceptualized as a set of subjective experiences and evaluations, which are relatively stable and interpreted as symptoms of good mental health. Fourteen constructs were identified as common lower-order indicators of well-being across measures: happiness, vitality, calmness, optimism, involvement, self-awareness, self-acceptance, self-worth, competence, development, purpose, significance, self-congruence and connection. The hypothesized properties of the higher- and lower-order factors were then tested in three studies. Study 1 developed an item pool and assessed the adequacy of its content by consulting a panel of six academics with expertise in well-being research. Studies 2 and 3 recruited two adult North American samples (total N = 1,496) to assess the questionnaire’s psychometric properties, and specifically its dimensionality, reliability, measurement invariance, and relationships with external criteria. Each lower-order scale fit a unidimensional model and all fourteen scales fit a correlated-factors model as well as higher-order and bifactor models. Evidence of measurement invariance was found across gender, age and a longitudinal period of 5 weeks. Lower- and higher-order scale scores showed adequate internal and test-retest reliabilities. Finally, lower- and higher-order scale scores showed strong associations with previous measures of similar constructs and lower associations with measures of distinct constructs. The questionnaire aims to contribute to future research both as a global measure of well-being as well as a collection of fourteen individual health-related scales.